2009
DOI: 10.1051/0004-6361/200912318
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a long-term trend in total solar irradiance

Abstract: Aims. During the solar minimum of 2008, the value of total solar irradiance at 1 AU (TSI) was more than 0.2 Wm −2 lower than during the last minimum in 1996, indicating for the first time a directly observed long-term change. On the other hand, chromospheric indices and hence solar UV irradiance do not exhibit a similar change. Methods. Comparison of TSI with other activity parameters indicates that only the open solar magnetic field, B R , observed from satellites at 1 AU show a similar long-term behaviour. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
201
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(215 citation statements)
references
References 34 publications
9
201
5
Order By: Relevance
“…The PMOD composite includes three periods of high solar activity called solar maxima (around the years 1980, 1991, 2002) and low solar activity called solar minima (around the years 1986, 1996, 2009). While TSI during the first two solar minima (1986 and 1996) was practically constant, it dropped significantly from the minimum level as observed in 1996 by about 0.2 W m 2 (140 ppm) in the solar minimum of 2009 (Fröhlich 2009a).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…The PMOD composite includes three periods of high solar activity called solar maxima (around the years 1980, 1991, 2002) and low solar activity called solar minima (around the years 1986, 1996, 2009). While TSI during the first two solar minima (1986 and 1996) was practically constant, it dropped significantly from the minimum level as observed in 1996 by about 0.2 W m 2 (140 ppm) in the solar minimum of 2009 (Fröhlich 2009a).…”
Section: Introductionmentioning
confidence: 76%
“…IRMB composite (Institut Royal Météorologique Belgique) (Dewitte et al 2004), 3. PMOD composite (PhysikalischMeteorologisches Observatorium Davos) (Fröhlich 2006) As is discussed in Fröhlich (2006Fröhlich ( , 2009a, the ACRIM and the IRMB composites show unreasonable behavior in time, whereas the PMOD composite does not. Therefore we restrict ourselves in this study on the PMOD composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship is more indirect than that with GCR flux in that F S is a small, and potentially variable, fraction of the field that threads the photosphere and thereby modulates the visible/IR emission of Sun (via the darkening effects of sunspots and the brightening effect of smaller magnetic flux tubes called faculae: Solanki et al 2005;Wenzler et al 2006). F S correlates well with TSI over the solar cycle (Lockwood and Stamper 1999;Lockwood 2002), and recent studies indicate that observed TSI does also reflect some of the longer-term drift in F S (Fröhlich 2009). Modelling of the long-term variations (since the Maunder Minimum) in F S and TSI Wang et al 2005) provides support for the broad correlation between the two.…”
Section: Paleoclimate Studies and Solar Proxiesmentioning
confidence: 96%
“…It has also been a deep minimum; the lowest ssn was 1.7, whereas the lowest ssn at the end of cycle 22 was 12.6. M. Dikpati ( ) HAO/NCAR, 3080 Center Green, Boulder, CO 80301, USA e-mail: dikpati@hao.ucar.edu The effect of this unusually long, deep minimum has been observed in various other solar cycle indices, such as in f10.7 radio flux, total solar irradiance (TSI) (Fröhlich 2009;Domingo et al 2009), atmospheric neutral density (Solomon et al 2010), as well as in the trend of solar p-mode frequency (Tripathy et al 2010) and torsional oscillation (Howe et al 2009). These unusual features observed in cycle 23 are most likely due to the dynamo operating in a somewhat different fashion compared to the previous cycles.…”
Section: Introductionmentioning
confidence: 99%